Fish–macrophyte relationship in the Anavilhanas Archipelago, a black water system in the Central Amazon - Araújo-Lima, Carlos Alberto Rego Monteiro; Portugal, L. P S; Ferreira, E. G. (Journal of Fish Biology, 1986)
The characin fish fauna associated with floating meadows on the floodplain of the Rio Negro was studied at the beginning of the rising water period. Two microhabitats were identified in the meadows (Paspalum plus Oryza vegetation and pure Oryza vegetation) and their influence on characin abundance tested. No significant difference in characin numbers was found between microhabitats. Three species accounted for 82% of characins captured: Hemigrammus levis, Metynnis cf. hypsauchen and Moenkhausia lepidura. Metynnis cf. hypsauchen was more abundant in Paspalum plus Oryza vegetation than in the other microhabitat. A similar difference was not found for H. levis and M. lepidura. The diets of the three species were similar in the smaller size classes, consisting primarily of Cladocera. However, the diets differed in the larger size classes with M. cf. hypsauchen foraging mainly on filamentous algae, M. lepidura on wild rice and H. levis on Cladocera. The diet shift is apparently an optimal foraging strategy, while the differences in microdistribution appear to be related to predation risk. Copyright © 1986, Wiley Blackwell. All rights reserved
Keywords: Cladocera; Hemigrammus Levis; Metynnis Hypsauchen; Moenkhausia Lepidura; Oryza; Paspalum; Rio Negro